Langerhans cell histiocytosis: current advances in molecular pathogenesis - Sconocchia, Tommaso; Foßelteder, Johannes; Sconocchia, Giuseppe; Reinisch, Andreas (Frontiers in Immunology, 2023)
Langerhans cell histiocytosis (LCH) is a rare and clinically heterogeneous hematological disease characterized by the accumulation of mononuclear phagocytes in various tissues and organs. LCH is often characterized by activating mutations of the mitogen-activated protein kinase (MAPK) pathway with BRAFV600E being the most recurrent mutation. Although this discovery has greatly helped in understanding the disease and in developing better investigational tools, the process of malignant transformation and the cell of origin are still not fully understood. In this review, we focus on the newest updates regarding the molecular pathogenesis of LCH and novel suggested pathways with treatment potential.